Parallel radiofrequency transmission at 3 tesla to improve safety in bilateral implanted wires in a heterogeneous model. Issue 6 (28th February 2017) - McElcheran, Clare E.; Yang, Benson; Anderson, Kevan J.T.; Golestanirad, Laleh; Graham, Simon J.
Abstract : Purpose: Elongated implanted conductors can interact with the radiofrequency (RF) transmission field during MRI, posing safety concerns of excessive heating in patients with deep brain stimulators. A technique using parallel RF transmission (pTx) is evaluated on an anthropomorphic heterogeneous model with bilateral and unilateral curved wires. Methods: Amplitude and phase were optimized by simulation to minimize heating surrounding the implanted wires and to minimize B 1 + inhomogeneity for four‐channel and eight‐channel pTx in a heterogeneous model. MRI experiments were conducted in an equivalent test phantom created from a common digital mesh file. Results: In four‐channel pTx, maximum local specific absorption rate (SAR) was reduced in both unilateral and bilateral wires by 47% and 59%, respectively, but with compromised B 1 + homogeneity. Optimized eight‐channel pTx substantially reduced local SAR compared with birdcage coil RF excitation in both unilateral and bilateral wires (reduction of maximum local SAR of 79% and 87%, respectively). B 1 + inhomogeneity was limited to 17% and 26%, respectively. Experimental validation with four‐channel pTx showed 80% and 92% temperature reduction at the tips of wire 1 and wire 2, respectively. Conclusion: This pTx approach yields promising reductions in local SAR at the tips of unilateral and bilateral implanted wires while maintaining image quality in simulation and experiment. Magn Reson Med 78:2408–2415, 2017. © 2017 International Society for Magnetic Resonance in Medicine.